2018
DOI: 10.1155/2018/2047981
|View full text |Cite
|
Sign up to set email alerts
|

Association of Colecalciferol, Ferritin, and Anemia among Pregnant Women: Result from Cohort Study on Vitamin D Status and Its Impact during Pregnancy and Childhood in Indonesia

Abstract: Studies had shown that iron-cycling was disturbed by inflammatory process through the role of hepcidin. Pregnancy is characterized by shifts of interleukin. Our objective was to determine if 25(OH) vitamin D (colecalciferol) status was associated with ferritin, anemia, and its changes during pregnancy. Method. A cohort study was done in 4 cities in West Java, Indonesia, beginning in July 2016. Subjects were followed up until third trimester. Examinations included were maternal ferritin, colecalciferol, and hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
1
19
1
2
Order By: Relevance
“…The prevalence of vitamin D deficiency among pregnant women ranges from 20 to over 90% . Previous research conducted in Bandung, Cimahi, Sukabumi and Waled stated that 75.6% of pregnant women experience vitamin D deficiency (<20 ng/mL) in the first trimester . Women are at increased risk of experiencing these conditions because of poor dietary intake, prolonged indoor stay and reduced ultraviolet exposure due to cultural clothing practices.…”
mentioning
confidence: 99%
“…The prevalence of vitamin D deficiency among pregnant women ranges from 20 to over 90% . Previous research conducted in Bandung, Cimahi, Sukabumi and Waled stated that 75.6% of pregnant women experience vitamin D deficiency (<20 ng/mL) in the first trimester . Women are at increased risk of experiencing these conditions because of poor dietary intake, prolonged indoor stay and reduced ultraviolet exposure due to cultural clothing practices.…”
mentioning
confidence: 99%
“…Another report concluded that maternal anemia increased the risk for small for gestational babies [ 4 ]. The cohort study in which this study was nested also reported high prevalence of anemia and hypovitaminosis D and intrauterine growth restriction (10%) [ 5 7 ]. Reports stated that the prevalence of anemia increased by gestational age [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 97%
“…Reports stated that the prevalence of anemia increased by gestational age [ 5 , 8 ]. In the pregnancy cohort of this study, anemia had 4-fold increase of prevalence in the third trimester, and relative risk (95% CI) for anemia in the third trimester among subjects with vitamin D deficiency and insufficiency in the first trimester (combined) was 2.96 (0.36–24.63) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations